Analysis of spatial and temporal evolution and drivers of cropland in the economic zone of the northern slope of Tianshan mountain - Xiang Qiao; Hongguang Liu; Yang Liu; Ping Gong; Pengfei Li; Ling Li (Environmental Research Communications, 2023)
The rapid population growth has intensified the need for increased food production, making cropland resources crucial for ensuring food security. Comprehending the evolutionary trends of cropland resources can aid in making well-informed decisions concerning their judicious utilization and contribute to the enhancement of ecological stability. In this investigation, the focus was directed towards the economic zone of the northern slope of Tianshan Mountain, situated in the arid expanse of northwest China. By analyzing land use data from 2000 to 2020, a range of methodologies, including Lorenz curves, local spatial autocorrelation, and Geodetector were employed to investigate the spatial and temporal distribution patterns, evolution, driving forces, heterogeneity, and driving mechanisms of cropland in this region. The findings revealed that the cropland in research area underwent three distinct stages: steady expansion, rapid expansion, and relative stability. The overall annual increase rate was 11.993%, primarily driven by the conversion of grassland and unused land. The spatial distribution of cropland resources was uneven, with concentrations in the central oasis plains in the form of strips and patches. The center of gravity of cropland exhibited a circular movement pattern of ‘northwest-southeast-northwest’. The migration speed followed a sequence of ‘slow-fast-slow’, and the spatial distribution appeared scattered. The main driving forces influencing cropland change included mean annual temperature, elevation, total grain output and agricultural output value. Among these, socioeconomic factors (0.403, 0.430) exerted a greater influence on the spatial distribution of cropland compared to natural factors (0.167). Most interactions between the factors demonstrated non-linear enhancement and two-factor enhancement. The discoveries of this study can assist decision-makers in formulating conservation strategies for cropland based on the current status of cropland resources and drivers in different regions. Furthermore, these findings can stimulate the coordinated development of cropland, water resources, population, and industries, facilitating informed decision-making across various domains.